Motilimonas pumila sp. nov., isolated from the gut of sea cucumber Apostichopus japonicus. Issue 3 (28th January 2019) - Wang, Feng-Qing; Ren, Li-Hua; Lin, Yu-Wei; Sun, Guo-Hua; Du, Zong-Jun; Zhao, Jin-Xin; Liu, Xiao-Jing; Liu, Li-Juan
Abstract : A facultatively anaerobic and Gram-negative bacterium, designated strain PLHSC7-2 T, was isolated from the gut of sea cucumber Apostichopusjaponicus that had been collected from the coastal area of Yantai, China. The cells were rod-shaped and motile by means of polar flagella. The novel isolate grew optimally at 28–30 °C,  in the presence of 2.0–3.0 % (w/v) NaCl and at pH 7.0–7.5. The sole respiratory quinone was Q-8 and the major fatty acids were summed feature 3 (C16 : 1 ω7 c and/or C16 : 1 ω6 c ), C16 : 0 and C17 : 0 . The predominant polar lipids were phosphatidylethanolamine, phosphatidylglycerol and diphosphatidylglycerol. Phylogenetic analyses based on 16S rRNA gene sequences showed that strain PLHSC7-2 T was phylogenetically affiliated with the genus Motilimonas, and exhibited sequence similarity of 96.2 % to Motilimonas eburnea YH6 T . The DNA G+C content was 45.5 mol%. On the basis of phenotypic, phylogenetic and genetic distinctiveness, strain PLHSC7-2 T (=MCCC 1K03522 T =KCTC 62589 T ) was classified as a novel species within the genus Motilimonas, for which the name Motilimonas pumila sp. nov. is proposed.